(untitled) (Eurasian Journal of Humanities and Social Sciences, 2026)
This in the article independent education in the process future engineers informational and communicative competence development pedagogical conditions analysis Modern digital education in the environment students independent knowledge to take activity organization to grow important pedagogical from tasks one is considered . In the study informational and communicative competence content , its structural components and independent education in the process this competence to develop impact provider pedagogical factors studied . Also , independent education process organization in the process of digital technologies , electronics education resources and innovative pedagogical from methods of use efficiency based on given . Research results engineering in education independent education efficiency increase and students information with work competencies to develop service does .